The big picture: mining the student data resource to inform learning development provision - Elizabeth Tanguay (Association for Learning Development in Higher Education (ALDinHE), 2017)
Accurately assessing student needs is a key concern for learning developers in order for provision to have a strong evidence base. Studies investigating student study needs in higher education tend to provide a snapshot in time and are limited to a certain number of students (Liu et al., 2011; Sloan et al., 2013). Others have surveyed users of learning development centres, but not their needs (Buchanan, 2015).